Peningkatan Minat Membeli Ulang Produk Bancassurance melalui Customer Engagement - Hartono, Pierdijono; Hurriyati, Ratih; Medidjati, R. Adam (Image : Jurnal Riset Manajemen, 2023)
The current sales of bancassurance have become a profitable business for both banks and insurance companies. To increase bancassurance sales, there is a need for sales to new customers who do not yet have insurance and for sales to customers who already have insurance to repurchase. The aim of this study is to investigate the influence of consumer perception, customer satisfaction, and service quality on the repurchase intention of bancassurance products through customer engagement. The sample was selected using the Consecutive Sampling technique, with a total of 353 respondents processed in Jakarta and Bandung. The data were analyzed using Multiple Linear Regression Analysis and Path Analysis through the SPSS application. The results of the study indicate that the variables of Consumer Perception, Customer Satisfaction, and Service Quality have a significant influence, both partially and simultaneously, on the Repurchase Intention of Bancassurance products through Customer Engagement as an intervening variable.